Principles of administrative judiciary in Ukraine - Leheza, Yevhen; Shamara, Oleksandr; Chalavan, Viktoria (DIXI, 2021)
Purpose: This article is devoted to scientific and theoretical research of modern system of principles for ad-ministrative procedural law in updated conditions of the Ukrainian state development, based on the needs of qualitative provision and realization of legal rights, freedoms and interests of natural and legal persons, in the sphere of public and legal relations. Main content: The author analyzed the administrative law regulations, and the doctrine of administrative proce-dural law as for determining nature and significance of the basic principles, which define the nature, structure, social orientation, and basic properties of legal regulation of this branch of law, and which on the other side create appropriate organizational and functional conditions for administrative procedural activities. Methodology: Materials and methods for research were based on the analysis of documentary sources. The basis is the dialectical method of cognition of the facts of social reality, on which the formal legal and compa-rative legal approaches are largely based. Conclusions: The principles of administrative procedural law can be divided into those that directly reflect the specifics and content of this branch of law, determine its features, purpose, objectives and intention, as well as administrative procedural principles, i.e., basic principles enshrined in administrative procedural law, which do not undergo significant changes, nor determine the nature and content of the activities of all subjects of administrative procedural legal relations.